Analysis and Performance of Cache Using Persisted Java Topics - Sharma, Ankush; Gupta, Vishal (International Journal of Computer Sciences and Engineering, 2025)
In most of the applications in today’s world, data is fetched from the secondary storage i.e. hard disk. The user connects directly to the database for fetching the data. In current approach of cache management and loading, data is loaded from the secondary storage i.e. from the database to the primary storage i.e. cache. In case of any cache failure, entire data has to be reloaded from the database which consumes a lot of time in case the volume of data runs into millions. In the proposed design, data will be fetched from cached data and will be displayed to the end user. In this design of the cache reload we will be persisting the cached objects in some persistent storage as jms topics or flat files. The cache will be rebuilt again from these objects rather than from the database in case of any cache failures. In addition to it, analysis and performance of cache has been shown in this paper considering various parameters.